A dança como uma prática educacional em crianças com Transtorno do Espectro Autista – TEA - Simas, Neiva Samara de Araújo (Brasil, 2023)
The research shows the actions of dance in a municipal school in Parintins in Baixo Amazonas, as an educational practice in children with Autistic Spectrum Disorder - ASD, in order to analyze it as an artistic language and not just as a curricular component of Art. The research at first assumes a bibliographic character in data collection in: magazines and periodicals existing in the Capes portal database, Scielo, database of theses and dissertations from Brazilian universities and books in the area under study that deal directly with the theme and build in this debate a reflection on the relationship between Autistic Spectrum Disorder and dance. In the second moment, the research is directed to the observational field for a better analysis of the data. From a qualitative perspective, we seek to understand the impacts of movements and body rhythms on autistic children from different perspectives and points of view. The need to dialogue with this theme is to discuss the relevance of dance as artistic languages ​​with children with ASD. This practice contributes to the development of body expression, language, social and cognitive aspects of children with ASD, as well as a more playful perception of the child who relates to the world through the body.